OPTN/SRTR 2017 Annual Data Report: Heart. (27th February 2019) - Colvin, M.; Smith, J. M.; Hadley, N.; Skeans, M. A.; Uccellini, K.; Lehman, R.; Robinson, A. M.; Israni, A. K.; Snyder, J. J.; Kasiske, B. L.
Abstract: In 2017, 3273 heart transplants were performed in the United States. New listings continued to increase, and 3769 new adults were listed for heart transplant in 2017. Over the past decade, posttransplant mortality has declined. The number of new pediatric listings increased over the past decade, as did the number of pediatric heart transplants, although some fluctuation has occurred more recently. New listings for pediatric heart transplants increased from 481 in 2007 to 623 in 2017. The number of pediatric heart transplants performed each year increased from 330 in 2007 to 432 in 2017, slightly fewer than in 2016. Short‐term and long‐term mortality improved. Among pediatric patients who underwent transplant between 2015‐2016, 4.8% had died by 6 months and 6.2% by 1 year.